Imagined Comunities Pemuda dalam Merubah Bantaran Sungai Menjadi Wisata Edukasi di Desa Rambipuji - Meydina Tri Luvianasari; Halimah Nur Churil Aini; Mohamad Helmi Wakhit Yansyah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Youth is the driving force of all civilizations born in the culture of society. The state of maturity affects the mindset and behavior. Sensitivity is very high in sniffing out various problems of the surrounding reality. The effectiveness of this sense is what drives the sensitivity to make changes to overcome various conditions. Based on this phenomenon, researchers use Benedict Anderson's Imagined Communities as a tool for analysis. Anderson said that collective imagination or imagination will bring into a shared awareness. In addition, youth are the driving force, because they have the opportunity to change the conditions of their society. This study uses a qualitative method with an ethnographic approach. This is in line with the analysis that seeks to describe and explain the reality that exists within a scope of society.